2020
DOI: 10.1186/s12889-020-09357-2
|View full text |Cite
|
Sign up to set email alerts
|

“Public health is global”: examining Indian stakeholders’ perspectives on Global Health education

Abstract: Background: Global health education has attracted significant attention in recent years from academic institutions in developed countries. In India however, a recent analysis found that delivery of global health education is fragmented and called for academic institutions to work towards closing the developing country/developed country dichotomy. Our study explored the understanding of global health in the Indian setting and opportunities for development of a global health education framework in Indian public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Embracing these frameworks can play a key role in capacitating the next generation of public health leaders. Although there remains work ahead, India has substantial potential to align education with sustainable development and global health priorities [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Embracing these frameworks can play a key role in capacitating the next generation of public health leaders. Although there remains work ahead, India has substantial potential to align education with sustainable development and global health priorities [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Embracing these frameworks has potential to play a key role in capacitating the next generation of public health leaders. Although there remains work ahead, India has substantial potential to align education with sustainable development and global health priorities (23).…”
Section: Discussionmentioning
confidence: 99%
“…In India, 95 institutions were identified that provide MPH programs of 2 years duration with English as the medium of instruction. The number of MPH programs has increased dramatically during the last two decades and specifically over the last couple of years with the onset of the COVID-19 pandemic (15). However, it is necessary to recognize that the curricula and criteria for admissions in these programs are diverse (16).…”
Section: Indiamentioning
confidence: 99%